Optimization of antioxidants in Curcuma zedoaria (Christm.) roscoe leaves and their functional cosmetic properties - Azahar, Nur Fauwizah (2017)
Medicinal plants especially leaves are an ample source of numerous pharmacologically active molecules. Therefore, continuous exploration from the leaves of Curcuma zedoaria has been extensively probe for its therapeutic value. In this study, the fourier transform infrared (FTIR) spectroscopy analysis was employed and it is found that the compounds present in the zedoary leaves samples are carboxylic acid, carbonyl, benzene and phenol. The levels of mineral content in zedoaria leaves were divided into two groups which are essential heavy metals; Mn (328.30 ppm), Fe (128.35 ppm), Cu (4.21 ppm), Ni (1.16 ppm), Cr (0.90 ppm) and non-essential heavy metals; (Pb) and (Cd) recorded to have 0.17 ppm and 0.03 ppm respectively which considered under permissible range for consumable medicinal plants. The extraction of antioxidants compounds from zedoary leaves were obtained by using response surface methodology (RSM). This method is used to optimize and simultaneously investigate the influence of condition variables such as temperature, time and solvent concentration towards highest total antioxidants assay. Result shows that at the optimized condition for high total antioxidants activity was found in zedoary leaves at 75οC, 92 mins and 90:10 v/v% ethanol concentrations exhibited (DPPH-radical scavenging (85.76%), β-carotene bleaching test (81.35%), ferric reducing antioxidant power assay (FRAP) (5.08 mM Fe2+ g/DW), total phenolic (125.75 mg/g GAE) and total flavonoid content (6.12 mg QE/g of extract). The optimized zedoary leaves were further explored for its functional cosmetics towards sun protection factor (SPF), anti-microbial test, anti-tyrosinase inhibition test, total carotenoids content, total ascorbic acid and total anthocyanin content. The results revealed that SPF value is 29.94 and fall into region UVC and UVB, the inhibition zone activity for bacteria Bacillus Sublis is7.0 mm at concentration100 mg mL-1, tyrosinase inhibition recorded to have 31% and total carotenoids content, ascorbic acid including anthocyanins content is 8.36 g BET/100 g, 1.2577 mg/100 g and 4.25 mg/100 g respectively. To conclude, there could be clear potential for the utilization of Curcuma zedoaria leaves as a good source of antioxidants for diverse cosmeceutical, medicinal and food additives applications.